Deep Water Polymastiidae (Porifera, Polymastiida) from the South West Pacific - Ekins, Merrick; Erpenbeck, Dirk; Wörheide, Gert; Hooper, John N.a. (Zootaxa, 2023)
This study reports on some deep water sponges in the family Polymastiidae collected during the 2017 Abyss Cruise off the East Coast of Australia and the 2003 NORFANZ Expedition to the Lord Howe and Norfolk Ridges in the Tasman Sea, Southwest Pacific Ocean. Species of Radiella, Spinularia, Ridleia, Tentorium and Polymastia were collected from abyssal and bathyal depths. From these collections, seven new species were discovered: Radiella nidula sp. nov., Radiella pumix sp. nov., Radiella sclera sp. nov., Spinularia flagellata sp. nov., Tentorium labium sp. nov., Ridleia echidna sp. nov. and Polymastia norfanzii sp. nov. In addition, two species previously known are redescribed based on the new collections: viz. Polymastia zitteli and Polymastia invaginata.